Causal relationship between gut microbiota and hidradenitis suppurativa: a two-sample Mendelian randomization study - Liu, Chengling; Liu, Xingchen; Li, Xin (Frontiers in Microbiology, 2024)
Background: Accumulating evidence suggests that alterations in gut microbiota composition are associated with the hidradenitis suppurativa (HS). However, the causal association between gut microbiota and HS remain undetermined.We performed a bidirectional two-sample Mendelian randomization (MR) analysis using genome-wide association study summary data of gut microbiota and hidradenitis suppurativa from the MiBioGen consortium which concluded 18,340 individuals analyzed by the MiBioGen Consortium, comprising 211 gut microbiota. HS data were acquired from strictly defined HS data collected by FinnGenbiobank analysis, which included 211,548 European ancestors (409 HS patients, 211,139 controls). The inverse variance weighted method (IVW), weighted median (WME), simple model, weighted model, weighted median, and MR-Egger were used to determine the changes of HS pathogenic bacterial taxa, followed by sensitivity analysis including horizontal pleiotropy analysis. The MR Steiger test evaluated the strength of a causal association and the leave-one-out method assessed the reliability of the results. Additionally, a reverse MR analysis was carried out to seek for possible reverse causality.Results: By combining the findings of all the MR steps, we identified four causal bacterial taxa, namely, Family XI, Porphyromonadaceae, Clostridium innocuum group and Lachnospira. The risk of HS might be positively associated with a high relative abundance of Clostridium innocuum group (Odds ratio, OR 2.17, p=0.00038) and Lachnospira (OR 2.45, p=0.017) but negatively associated with Family XI (OR 0.67, p=0.049 ) and Porphyromonadaceae(OR 0.29, p=0.014). There were no noticeable outliers, horizontal pleiotropy, or heterogeneity. Furthermore, there was no proof of reverse causation found in the reverse MR study.This study indicates that Clostridium innocuum group and Lachnospira might have anti-protective effect on HS, whereas Family XI and Porphyromonadaceae might have a protective effect on HS. Our study reveals that there exists a beneficial or detrimental causal effect of gut microbiota composition on HS and offers potentially beneficial methods for therapy and avoidance of HS.